2014
DOI: 10.1007/s10198-014-0560-1
|View full text |Cite
|
Sign up to set email alerts
|

Orphan drugs policies: a suitable case for treatment

Abstract: Context Current orphan drug policies are unsatisfactory when viewed from almost all perspectives. Patients find that, although therapies are available for many rare conditions, access to care is sometimes restricted. Pharmaceutical manufacturers have responded to the incentives for research embodied in orphan drug legislation, only to find that funds are not made available to pay for therapies once developed. Those funding health care find that most orphan drugs do not justify funding based on standard value f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 25 publications
0
87
1
Order By: Relevance
“…Health technology assessment (HTA) [18] , as described by Lampe et al [19] , is intended to identify, appraise, and synthesise all available scientific evidence to inform decisions considering 10 different domains: characterisation of the specific health problem and existing current treatment alternatives; description of the technology under scrutiny; evidence on safety, clinical effectiveness (comparative effectiveness), and costeffectiveness; budget impact analysis; ethical analysis; and considerations of organisational, social, and legal issues. In the case of ODs, several of the above-reported domains become critical [9,12,[20][21][22][23][24][25] , feeding an open worldwide debate about the appropriateness of existing HTA methods for health technologies devoted to RDs [26][27][28][29] . Increasingly, considerations of using an extended set of criteria beyond the conventional core assessment of safety, efficacy, and cost-effectiveness is gaining acceptance even among the HTA community [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Health technology assessment (HTA) [18] , as described by Lampe et al [19] , is intended to identify, appraise, and synthesise all available scientific evidence to inform decisions considering 10 different domains: characterisation of the specific health problem and existing current treatment alternatives; description of the technology under scrutiny; evidence on safety, clinical effectiveness (comparative effectiveness), and costeffectiveness; budget impact analysis; ethical analysis; and considerations of organisational, social, and legal issues. In the case of ODs, several of the above-reported domains become critical [9,12,[20][21][22][23][24][25] , feeding an open worldwide debate about the appropriateness of existing HTA methods for health technologies devoted to RDs [26][27][28][29] . Increasingly, considerations of using an extended set of criteria beyond the conventional core assessment of safety, efficacy, and cost-effectiveness is gaining acceptance even among the HTA community [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…One issue has become relevant given advances in personalised medicine where a subset of the patient population can be defi ned by the existence of a biomarker [ 16 ]. This might lead to the fact that applicants for orphan designation will 'salami slice' treatment indications in order to qualify for orphan status [ 17 ].…”
Section: Subsetting/valid Conditionmentioning
confidence: 99%
“…(12) Little evidence in support of a societal preference for rare conditions exists, and the few studies that attempted to elucidate this suggested the contrary when patients with more common diseases were denied treatment in order to treat fewer patients with a rare condition. (12)(13)(14)(15) In such cases, these decisions partly rely on the decision-makers' willingness to accept high ICERs based on additional factors that influence their judgment of (scientific and social) value, such as, for example, disease severity, the treatment's orphan status, or to what extent evidence characterised by uncertainty is acceptable. (16) They also rely on the flexibility of these processes in, for example, their ability to implement managed entry agreements or the availability of separate funding programs (e.g.…”
Section: Introductionmentioning
confidence: 99%